The Chemistry of Metal–Organic Frameworks. Synthesis, Characterization, and Applications, 2 Volumes. Edited by Stefan Kaskel. Issue 6 (11th January 2017) - Burrows, Andrew D.
Abstract : Wiley‐VCH, Weinheim 2016. 904 pp., hardcover, € 299.00.—ISBN 978‐3527338740